1990
DOI: 10.1002/cne.903020413
|View full text |Cite
|
Sign up to set email alerts
|

Sources of presumptive glutamatergic/aspartatergic afferents to the magnocellular basal forebrain in the rat

Abstract: The distribution of presumptive glutamatergic and/or aspartatergic neurons retrogradely labeled following injections of [3H]-D-aspartate into the magnocellular basal forebrain of the rat was compared with the distribution of neurons labeled by comparable injections of the nonspecific retrograde axonal tracer wheat germ agglutinin conjugated to horseradish peroxidase. Cells retrogradely labeled by wheat germ agglutinin-horseradish peroxidase were found in a wide range of limbic and limbic-related structures in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 158 publications
6
76
0
Order By: Relevance
“…PHA-L injections in the NId labeled a similar but less dense projection to the septal region. A projection from the region of the NI to the medial-diagonal band complex is well established with retrograde tract-tracing methods (Segal and Landis, 1974;Semba et al, 1988;Vertes, 1988;Carnes et al, 1990). Our anterograde tracer analysis has expanded these results by showing that fibers arising from both the NIc and NId are preferentially distributed toward the lateral borders of the medial septal nucleus and tend to avoid its central core.…”
Section: Neuronal Outputs Of the Nimentioning
confidence: 68%
“…PHA-L injections in the NId labeled a similar but less dense projection to the septal region. A projection from the region of the NI to the medial-diagonal band complex is well established with retrograde tract-tracing methods (Segal and Landis, 1974;Semba et al, 1988;Vertes, 1988;Carnes et al, 1990). Our anterograde tracer analysis has expanded these results by showing that fibers arising from both the NIc and NId are preferentially distributed toward the lateral borders of the medial septal nucleus and tend to avoid its central core.…”
Section: Neuronal Outputs Of the Nimentioning
confidence: 68%
“…In ultrastructural studies of identified cholinergic basal forebrain neurones, it has been found that the synaptic input to these cells is greatest on the dendrites and, in fact, of the highest density upon the distal dendrites (Ingham, Bolam, Wainer & Smith, 1985). Multiple forebrain and brainstem neurones project into the region of the basal forebrain cholinergic neurones and their dendrites (Grove, 1988;Jones & Cuello, 1989) and many of these neurones may release an excitatory amino acid from their terminals (Carnes et al 1990). The basalis neurones appear to receive input, primarily to their dendrites, from the neocortex (Saper, 1984;Lehmann & Saper, 1985), and the cortical projection neurones are known to contain high concentrations of glutamate and glutaminase, a synthetic enzyme for glutamate (Ottersen & Storm-Mathisen, 1984;Kaneko & Mizuno, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Such NMDAinduced rhythmic firing has been shown (in vivo or in vitro) for cells located in the spinal cord (Wallen & Grillner, 1987), the nucleus tractus solitarius (Tell & Jean, 1991), the medial vestibular nucleus (Serafin, Khateb, de Waele, Vidal & Miihlethaler, 1992), the abducens nucleus (Durand, 1993), the substantia nigra (Johnson, Seutin & North, 1992;Chergui et al 1993), the caudate nucleus (Herrling, Morris & Salt, 1983), the supraoptic nucleus (Hu & Bourque, 1992), the thalamus (Leresche, Lightowler, Soltesz, JassikGerschenfeld & Crunelli, 1991) and the cerebral cortex (Flatman, Schwindt, Crill & Stafstrom, 1983). Since the basal forebrain is thought to receive an important contingent of glutamatergic fibres from the brainstem reticular formation and from the cerebral cortex (Carnes, Fuller & Price, 1990;Jones, 1994), it would be possible that glutamate, acting on NMDA channels, might also induce rhythmic bursting in nucleus basalis cholinergic neurones. Our results indeed demonstrated that NMDA, and not agonists of the other glutamate receptors, induced the cholinergic neurones. This action depended predominantly on the presence of powerful low-threshold Ca2+ spikes in the cholinergic cells, and differed accordingly in temporal characteristics and ionic mechanisms from that reported for other systems.…”
mentioning
confidence: 99%
“…If so, an important role of the NT-induced rhythmic bursts may be that of modulating slow forebrain rhythms. The BF projects heavily upon the cortical mantle and receives a direct cortical feedback (Lemann and Saper, 1985;Cames et al, 1990). In addition, both cholinergic and noncholinergic BF neurons project upon the thalamic nucleus reticularis (Steriade et al, 1987), which is a key element in the generation of different forms of oscillatory rhythms in the thalamocortical network (Steriade et al, 1985(Steriade et al, , 1986(Steriade et al, ,1993Steriade and Llinls, 1988;von Krosigk et al, 1993).…”
Section: Nt Internalizationmentioning
confidence: 99%